Seminar Online Memahami Esensi Penelitian Kuantitatif - Faishol, Muhammad (Journal Of Human And Education (JAHE), 2024)
The online seminar "Understanding the Essentials of Quantitative Research," which was held on January 21 2024, aims to increase students' understanding of quantitative research methodology throughout Indonesia. This event consists of an introductory session, core material, and analytical tools practice, which involves conveying basic concepts, research design, and statistical analysis techniques through interactive presentations and case studies, followed by a question and answer session and hands-on applications using tools such as SPSS. The evaluation results showed that the seminar was effective in delivering the material, with 70% of participants showing good understanding, however there were challenges in the practical sessions which indicated the need for additional technical support and adaptation of the material for the different levels of knowledge of the participants.